Investigating anaemia vulnerability: determinants and changes in prevalence among adolescent girls in aspirational districts of India - Subhojit Let; Mahashweta Chakrabarty; Seema Tiwari (Humanities & Social Sciences Communications)
Abstract The World Health Organization identifies adolescent girls as particularly prone to anaemia due to reproductive changes, with challenges being more pronounced in India’s ‘Aspirational Districts’ (ADs), which suffer from poor education and health. The study examines the prevalence of anaemia among adolescent girls in ADs and identifies associated determinants from 2015 to 2021. Data from the National Family Health Survey (NFHS)-4 and NFHS-5, covering 21,637 and 19,879 adolescent girls aged 15–19 in ADs, were analyzed. Multivariable logistic regression was used to identify the determinants of anaemia among adolescents. The results show a notable increase in anaemia among adolescent girls in ADs, where anaemia rates have climbed from 58.3% to 62.4%, surpassing the national average rise. Over this period, more than 65% of ADs saw an uptick in anaemia prevalence, affecting 75 out of 112 districts. Specifically, Barpeta in Assam recorded the highest increase in anaemia prevalence at 45.1% points, while Haridwar in Uttarakhand reported a decrease of 25.8% points. Additionally, anaemia prevalence was found higher among girls with higher parity, Muslim girls, and those from poorer households. Pooled regression revealed that adolescent girls with a higher number of children (AOR: 1.29), formerly married (AOR: 1.57), Scheduled Tribe (ST) girls (AOR: 1.44), and girls with amenorrhoea (AOR: 1.57) were highly associated with anaemia. Specialized healthcare and nutrition programs for adolescent girls, similar to those for pregnant women in ADs, are crucial. Focusing on formerly married girls, ST girls, and those with amenorrhoea will enhance access to health resources, reduce anaemia rates, and improve overall well-being.